Time and Workload Analysis to Determine Total Labor in the Arabica Coffee Harvesting Process - Fil'aini, Raizummi; Juanto, Benedictus; Attamimi, Tahani Farhat; Valentino, Fandy; Telaumbanua, Mareli; Sari, Tri Novita; Mufidah, Zunanik (Applied Research in Science and Technology, 2024)
Farmers verify ripe coffee cherries, pick them individually, and place them in the harvest basket in the coffee harvesting process. This task typically takes 7-8 hours. During harvesting, farmers experience a physical workload that impacts their work capacity. This research aims to measure the qualitative and quantitative workload levels of the coffee harvesting process, determine the working time based on the farmers' Human Output Capacity, and calculate the total number of daily workers needed to achieve daily coffee production targets. The determination of the number of daily workers is based on the work capacity of the farmers. Farmers were categorized into two age groups: productive age (30-40 years) and non-productive age (50-60 years). Data observed included heart rate during harvest, heart rate calibration data, subjects' body characteristics, and coffee productivity. The results showed that the heaviest workload, related to verifying ripe cherries, fell into the medium category, with an energy consumption level of 3,370 Kcal per minute. The optimal working time for the coffee harvesting process is 6 hours for workers of productive age and 4 hours for workers of non-productive age. To meet production targets, 9 workers of productive age and 10 workers of non-productive age are required.